Who has sheds? Exploring practices and determinants of overnight housing for backyard poultry in rural Bangladesh to inform an intervention to limit exposure to poultry and poultry feces. - Elizabeth D Thomas; Laura H Kwong; Nadia Ali Rimi; Ireen Sultana Shanta; Mohammad Rofi Uddin; Shifat Khan; Salma Akter; S M Monirul Ahasan; Mahbub-Ul Alam; Mahbubur Rahman; Tarique Md Nurul Huda; Peter J Winch (PLOS Global Public Health, 2025)
Backyard poultry-rearing contributes to income and food security for rural households in low- and middle-income countries. However, poultry are often kept inside the household dwelling at night, posing health risks to the people raising them. Housing poultry separately from the dwelling overnight is a potential intervention to limit exposure to poultry. The aim of this study was to describe practices and determinants of overnight poultry housing in rural Bangladesh as formative research for an intervention to separate young children from poultry and poultry feces. We conducted 19 transect walks in villages across Bangladesh to document overnight housing practices among backyard poultry raisers. We then conducted 27 semi-structured interviews to explore poultry-raising practices, including housing types and materials identified during transect walks. We found overnight poultry housing both inside and separate from the dwelling and found that most poultry raisers who kept their birds separate from the dwelling overnight did so in courtyard sheds. There was a preference and willingness to house birds outside, provided a shed was available, although overnight housing practices fluctuated. Having a shed was a function of household resources, including availability and access to materials and skilled labor, available physical space, area- and village-wide trends, and the preferences and concerns of poultry raisers. We recommend that future studies measuring human exposure to poultry and poultry feces assess exposure prospectively and at regular intervals to capture variations in housing practice, and include assessments of poultry housing hygiene practices. The promotion of sheds for overnight poultry housing may be an acceptable intervention approach in this setting, though programs will need to make recommendations for housing that address the risk of zoonotic disease transmission and accommodate the preferences and constraints of poultry raisers over a one-size-fits-all approach.